A new insight and improvement on deconvolution beamforming in spherical harmonics domain. (June 2021) - Chu, Zhigang; Yang, Yongxin; Yang, Yang
Highlights: A special matrix form of SHB compatible with all existing deconvolution methods is constructed. The effect of wavefield simulation order truncation for PSF on deconvolution methods is disclosed. A strategy to determine the wavefield simulation order truncation is proposed. Abstract: The existing deconvolution methods with spherical microphone arrays (SMAs) have not been implemented under a unified mathematical framework. In other words, they utilize different output expressions of spherical harmonics beamforming (SHB), which makes their application and popularization inconvenient. In this paper, the output of SHB is transformed into a special matrix form, which provides a unified mathematical framework for all existing deconvolution methods with SMAs. The point spread function (PSF) based deconvolution methods require two order truncations when computing PSFs. One is for the wavefield simulation, and the other is for SHB calculation. In previous works, the former is determined roughly according to the latter. In this paper, the effect of the wavefield simulation order truncation on the performance of deconvolution methods is disclosed. A convincing strategy to determine this order truncation is proposed. This work helps perfect deconvolution beamforming technology with SMAs.